Pelestarian Kawasan Tanjung Pura Sebagai Aset Wisata Di Kabupaten Langkat - Handayani Nasution, Meyga Fitri; Widya, Dharma (RUAS, 2014)
Tanjung Pura, formerly was the capital of Malay Sultanate of Langkat, had various cultural heritage of Malay Sultanate and Dutch colonial. Diversity of those objects (historic buildings and other relics) is potential for tourism. It needs conservation efforts. Specific target of this research is to preserve some area in Tanjung Pura to become asset of architectural and cultural tourism. Results of this research is design concept, preservation concept, regional planning and documentation (historic buildings photoes and pictures) by design program. The methods used in this study are direct observation, determining zones to take samples of historic buildings, measuring, making sketches and documents for every sample. The results of field measuring and sketching were represented using design program, to be analyzed and synthesized to propose design concept for certain area planned as tourist destination.Keywords: City Of Tanjung Pura, preservation, tourism architecture